Menopause and Body Composition: A Complex Field - Juppi, Hanna-Kaarina; Karppinen, Jari E.; Laakkonen, Eija K. (Seminars in Reproductive Medicine, 2025)
Given that menopause affects about half of the world's midlife population, it is crucial to understand its impact beyond traditional menopausal symptomology. For instance, many women, while transitioning through menopause, experience profound changes in body composition. These changes may contribute to postmenopausal reductions in metabolic health. This narrative review explores the influence of menopause on skeletal muscle and adipose tissue, highlighting the decline in muscle mass and strength and the gain and redistribution of adipose tissue, particularly the increase in visceral adiposity. Although menopausal changes in body composition are seemingly extensively studied, the longitudinal studies are not that common, and the precise mechanisms driving body composition changes remain unclear, with uncertainties surrounding the roles of hormonal shifts compared with regular aging, energy balance, and lifestyle factors. Notably, it remains debated whether menopause or estrogen meaningfully influences resting energy expenditure. The review also considers the potential mitigating effects of menopausal hormone therapy and regular exercise. Understanding these changes is essential for developing effective strategies to support women's health during and after menopause.
Keywords: menopausal transition; fat-free mass; fat mass; energy expenditure; energy balance